Scale-up methodology for automatic biomass furnaces. Issue 2 (April 2020) - Barroso, Gabriel; Nussbaumer, Thomas; Ulrich, Markus; Reiterer, Thomas; Feldmeier, Sabine
Abstract: This work presents a methodology to perform the scale-up of a solid fuel furnace to a higher heat output with maintaining or improving the burn-out quality. As basis to derive the scale-up concept, an example of a 35 kW screw burner for biomass fuels is investigated. Based on the Pi-theorem, the relevant dimensionless parameters are derived and similarity rules for the scale-up are proposed as follows: As initial conditions, the height to diameter ratio of the combustion chamber, the mean Reynolds number in the combustion chamber and the mean square velocity through the combustion chamber shall be kept constant or in the case of the Reynolds number may also increase. Additionally the effective momentum flux ratio between the secondary air injected in the combustion chamber and the gases from the pyrolysis and gasification section also shall be kept constant to maintain the mixing conditions between combustible gases and secondary air. Finally the thermal surface load on the screw also shall be kept constant. The influence of different scale-up approaches on thermal surface load, gas velocity, pressure losses, Reynolds number and height-to-diameter ratio are compared and discussed and a scaling approach to increase the heat output from 35 kW to 150 kW is described. For a theoretical validation of the scale-up, CFD simulations are performed to investigate the predicted pollutant emissions and the pressure loss for the scaled 150 kW furnace. Highlights: Scale-up concept derived using Pi-theorem. Keep constant Height-to-diameter ratio and mean velocity in the burning chamber. Keep constant or increase Reynolds number. Keep constant momentum flux ratio between primary and secondary air. Keep constant thermal surface load.